Konsep Kenabian dan Wahyu dalam Al-Qur’an: Kajian Teologis QS. An-Nisāʾ [4]: 136 - Syafirin, Muhammad (Jurnal Moderasi, 2021)
Prophethood and revelation are the two main pillars (asās al-ūla) in the texture of Islamic theology. Prophethood has an ideal role as an intermediary for al-Ḥaq to al-Khalq, while 'revelation' as a corpus of God becomes the legality of a prophethood (nubuwwah). This paper describes the theological study of prophethood and revelation in QS. an-Nisā' [4]:136 using thematic analysis upon the qur'an and its interpretation. The results of this study is the description of notion of prophethood and revelation in an inclusive manner (QS. Ghāfir [40] 78) in the Qur'an. Additionally, the dicta of faith towards both, at least 25 figures and four books and the two temperatures, have an urgent accentuation for individual Muslims, so that the denial of all or part of the details can have implications for the theological foundation power of a Muslim in religion. In addition, this study also elaborates the criteria that can be used as legitimacy of the truth of a prophet's nubuwwah, among others; first, the existence of 'revelation' (philosophical sacrality); second, a 'miracle' (superiority); Third, carrying out 'shari'ah' (constructivity of humanity).Kenabian dan wahyu merupakan dua pilar utama (asās al-ūla) dalam tekstur teologi Islam. Kenabian memiliki peranan ideal sebagai perantara al-Ḥaq kepada al-Khalq, sementara ‘wahyu’ sebagai korpus Tuhan menjadi legalitas atas suatu kenabian (nubuwwah). Tulisan ini menguraikan kajian teologis tentang kenabian dan wahyu dalam QS. an-Nisā’ [4]: 136 dengan menggunakan analisis tematik ayat dan interpretasi teks al-Qur’an. Hasil kajian ini mendeskripsikan pengertian kenabian dan wahyu secara inklusif (QS. Ghāfir [40] 78) dalam al-Qur’an. Kemudian, dikte perintah beriman terhadap keduanya, sekurang-kurangnya terhadap 25 tokoh dan empat kitab beserta dua suhuf itu, memiliki aksentuasi yang urgen bagi individual umat Islam, sehingga pengingkaran terhadap semua atau sebagian rinciannya dapat berimplikasi pada daya pondasi teologis seorang muslim dalam beragama. Selain itu, kajian ini juga mengelaborasi kriteria-kriteria yang dapat dijadikan legitimasi kebenaran nubuwwah seorang nabi, di antaranya; pertama, adanya ‘wahyu’ (sakralitas filosofis); kedua, diberikan ‘mukjizat’ (superioritas); ketiga, mengemban ‘syari’at’ (konstruktivitas kemanusiaan).